Food and Drug Administration insights on clinical study of weight‐loss devices intended for adolescent patients. Issue 7 (10th January 2021) - Marrone, April K.; Venkataraman‐Rao, Priya; Gottschalk, Laura
Summary: Background: Medical devices intended for weight loss may provide clinically meaningful benefit to children who are overweight and have obesity; however, no device has been approved by the U.S. Food and Drug Administration (FDA) for use in patients below 18 years of age. Encouragingly, FDA regularly sees new device designs because the field of weight‐loss devices is advancing rapidly. As more devices for weight loss are in development, their use in adolescent populations is expected to follow, but supporting data are needed. Objectives: This report describes efforts that FDA has taken to understand the unmet clinical need, understand how pediatric patients might benefit from a weight‐loss device, and provide considerations for how to best design weight‐loss device clinical studies considering device‐specific patient risk for adolescents. Methods: We review the recommendations provided to the FDA in 2005 via a Pediatric Advisory Committee meeting and discuss feedback received in 2018 through our Network of Experts programme. Results: FDA encourages weight‐loss device manufacturers and academic researchers to collect data through properly controlled trials so that more treatment options can be accessible to pediatric patients. Conclusions: FDA remains open to considering risk‐based clinical study designs incorporating pediatric patients and will continue to take into account the risk to adolescent study participants when determining whether the benefit–risk evidence supports initiation of an adolescent weight‐loss device study.